Improcedencia de la Determinación Complementaria en el Reclamo Administrativo Tributario porque no concuerda con las Garantías del Debido Proceso de la Constitución - Medina Medina, Amparo Soledad (2016)
This research topic is what made on the problems that exist in tax matters in relation to Tax Administrative Complaint which is interrupted by the action of the additional determination, which is a current problem in our social reality. For the development of this thesis I determined the general objective of Conduct a critical and analytical study of Book Two of the Tax Code of Administrative Procedure in relation to the Constitution the judicial guarantees, which was established through the application of methods and techniques scientific, that guided me to achieve results that allowed that the proposal for reform of law. More than doctrinal literature collection, surveys were conducted to thirty persons knowledgeable in the tax field in our city, to collect data that could be concluded that the Tax Administrative Complaint is affected once the administration intends to determine again the tax liability for the second, which is a problem for the taxpayer who feels affected by administrative decisions. You must make an amendment to the Tax Code, to ensure the rights of everyone to challenge administrative decisions as legal under the Constitution